Combined influence of meso-scale circulation and bathymetry on the foraging behaviour of a diving predator, the king penguin (Aptenodytes patagonicus). (February 2016) - Scheffer, Annette; Trathan, Philip N.; Edmonston, Johnnie G.; Bost, Charles-André
Highlights: Examination of the foraging behaviour of king penguins at the Kerguelen Plateau. Analysis of penguin behaviour combined with oceanography at the surface and at depth. Penguins foraged in a cold-water flow interacting with the Kerguelen Plateau. Surface and diving movements were directed into bathymetry-related oceanographic features. This behaviour has not been observed in other king penguin breeding locations. Abstract: Investigating the responses of marine predators to environmental features is of key importance for understanding their foraging behaviour and reproductive success. In this study we examined the foraging behaviour of king penguins breeding at Kerguelen (southern Indian Ocean) in relation to oceanographic and bathymetric features within their foraging ambit. We used ARGOS and Global Positioning System tracking together with Time–Depth–Temperature-Recorders (TDR) to follow the at-sea movements of incubating and brooding king penguins. Combining the penguin behaviour with oceanographic data at the surface through satellite data and at depth through in-situ recordings by the TDRs enabled us to explore how these predators adjusted their horizontal and vertical foraging movements in response to their physical environment. Relating the observed behaviour and oceanographic patterns to local bathymetry lead to a comprehensive picture of the combined influence of bathymetry and meso-scale circulation on the foraging behaviour of king penguins. During both breeding stages king penguins foraged in the area to the south-east of Kerguelen, where they explored an influx of cold waters of southern origin interacting with the Kerguelen Plateau bathymetry. Foraging in the Polar Front and at the thermocline was associated with high prey capture rates. However, foraging trip orientation and water mass utilization suggested that bathymetrically entrained cold-water features provided the most favourable foraging locations. Our study explicitly reports the exploration of bathymetry-related oceanographic features by foraging king penguins. It confirms the presence of Areas of Ecological Significance for marine predators on the Kerguelen Plateau, and suggests the importance of further areas related to the cold-water flow along the shelf break of the Kerguelen Plateau.